2008
DOI: 10.1603/0046-225x(2008)37[1224:ssoflc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Structure of Forest Lepidopteran Communities in Oak Hickory Forests of Indiana

Abstract: The response of forest insect communities to disturbances such as timber harvest will likely depend on the underlying spatial structure of species assemblages before the disturbance occurs. Unfortunately, many studies of forest management implicitly assume homogeneity of community structure before harvest; postlogging communities are inferred to be a direct product of the imposed management. The goal of this study is to examine variation in the community structure of forest Lepidoptera using the pretimber harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…These results suggest that widespread clearcutting of timber has a negative and long-lasting effect on species richness and abundance of forest-feeding Lepidoptera. Similar results were obtained from sampling forest stands in southern Ohio and Indiana (see Summerville and Crist, 2002;Summerville et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results suggest that widespread clearcutting of timber has a negative and long-lasting effect on species richness and abundance of forest-feeding Lepidoptera. Similar results were obtained from sampling forest stands in southern Ohio and Indiana (see Summerville and Crist, 2002;Summerville et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…In early 2007, Summerville et al (2008) identified three large forested landscapes within Morgan-Monroe State Forest for lepidopteran sampling. These landscapes possessed a comparable legacy of timber harvest; most were clearcut % 60-70 y in the past (Haulton, 2012).…”
Section: Heementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in southeastern Sweden (Jonason et al 2010), butterfly species richness (not the abundance) was found to be positively related to increasing tree cover in the farm landscape. Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SMZs promote sediment and nutrient trapping by slowing and often preventing entry into aquatic systems [53,100]. Appropriately managed and designed SMZs moderate light infiltration, dampen or minimize aquatic and terrestrial temperature gradients, slow nutrient flow, maintain hypoheic and hydrologic function, and preserve riparian vegetative composition and structure [2,15,[101][102][103][104][105][106].…”
Section: Streamside Management Zonesmentioning
confidence: 99%